Enhancing the mechanical properties of 3D printed polylactic acid using nanocellulose - Ambone, Tushar; Torris, Arun; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2020)
We report here a systematic investigation of the mechanical properties of polylactic acid (PLA) processed by fused filament fabrication (FFF) 3D printing vs PLA processed by compression molding. Our results show that the tensile strength and modulus of FFF-PLA is 49% and 41% lower, respectively, than compression molded samples of PLA. We also demonstrate here an approach to augment the mechanical properties of 3D printed PLA using nanocellulose. Incorporation of a small quantity (1 wt%) of cellulose nanofibers (CNF) was found to enhance the tensile strength and modulus of 3D printed PLA by 84% and 63%, respectively. X-ray microtomography was used to probe the morphology of 3D printed PLA and PLA/CNF composites. 3D printed PLA/CNF composites had significantly lesser voids as compared to neat 3D printed PLA. Differential scanning calorimetry study revealed that CNF can accelerate the nucleation and crystallization of 3D printed PLA leading to enhanced crystallinity. The thermal stability of 3D printed PLA/CNF composites was not compromised by the addition of CNF. The enhanced mechanical properties of 3D printed PLA/CNF composites can be ascribed to higher crystallinity and lesser defects.
Keywords: 3D printing; Biocomposites; composites; fused filament fabrication (FFF); Nanocellulose; polylactic acid (PLA)

Enhancing thermomechanical and chemical stability of polymer electrolyte membranes using polydopamine coated nanocellulose - Ram, Farsa; Velayutham, Parthiban; Sahu, Akhila Kumar; Lele, Ashish K.; Shanmuganathan, Kadhiravan (ACS Applied Energy Materials, 2020)
We report here an approach to enhance the chemical and thermomechanical stability of polymer electrolyte membranes without compromising proton conductivity. Multifunctional polydopamine coated nanocellulose (PNC) was prepared by oxidative polymerization of dopamine on nano cellulose fibers and subsequently incorporated in Nafion by solution blending. PNC had a very significant effect on the thermomechanical properties of Nafion showing up to 200% improvement in the storage modulus at 90 degrees C. The PNC network also enhanced the dimensional stability of Nafion under constant stress. The 3 wt % PNC composite membrane showed a drastic reduction in creep compliance of about 39.9% and 46.5% in J(max) at 30 degrees and 60 degrees C, respectively. Free radical scavenging properties of polydopamine also helped to significantly enhance the chemical stability of Nafion, which was ascertained by accelerated degradation tests conducted in Fenton's reagent at 70 degrees C over 40 days. F-19 CP MAS solid state NMR, FTIR, and tensile tests on the membranes show higher chemical stability of the 3 wt % PNC composite membrane. The proton conductivity of the 3 wt % PNC composite membrane at 90 degrees C and 100% RH (similar to 125 mS/cm) was slightly higher than the Nafion membrane (similar to 94 mS/cm) at similar conditions. The retention of proton conductivity even with lower water uptake could be ascribed to proton hopping through polydopamine coated nanocellulose. Performance of the composite membrane was also evaluated in a single stack fuel cell and found to be better than recast Nafion. The benefits derived by this approach are not restricted to Nafion alone and shall broadly apply to many other polymer membranes.
Keywords: cellulose nanofibers; chemical stability; dimensional stability; fuel cell; polydopamine; polymer electrolyte membrane

Elastic piezoelectric aerogels from isotropic and directionally ice-templated cellulose nanocrystals: comparison of structure and energy harvesting - Ram, Farsa; Biswas, Bipul; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Cellulose, 2021)
We report the preparation of highly compressible and elastic piezoelectric aerogels of carboxylated cellulose nanocrystals (CNCs). Aqueous CNC dispersions containing polyethyleneimine and crosslinker were frozen isotropically to yield isotropic aerogels, while oriented aerogels were prepared by directional freezing. These aerogels were highly flexible and porous (similar to 85% void fraction), exhibiting greater than 90% recovery at 50% compressive strain even after 100 compression-decompression cycles. Since such aerogels with low bulk modulus and high anisotropy would be an ideal platform for leveraging the piezoelectric properties of CNCs, we used them to prepare piezoelectric nanogenerator devices and determined their energy transduction behavior. Anisotropic aerogels led to an enhanced open-circuit voltage of 840 mV (at similar to 8 N applied force), which is over 2.6 times higher than isotropic aerogels (320 mV). The energy density of anisotropic aerogels was around 52 nW/cm(2), representing outstanding piezoelectric performance for cellulose-based aerogels. Such aerogels with high compressibility, elastic recovery and exceptional piezoelectric performance could have potential applications in sensors, wearable electronics, etc.
Keywords: Aerogel; Anisotropic; Cellulose nanocrystals; energy harvesting; Piezoelectricity

Enhancing the crystallization kinetics and mechanical properties of poly(lactic acid) blends for 3D printing application - Kothavade, Premkumar; Yadav, Prashant; Gopal, Animesh; Pol, Harshawardhan; Kafi, Abdullah; Bateman, Stuart; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2024)
3D printing of poly(lactic acid) (PLA) blends has been attempted to resolve issues such as inherent brittleness and slow crystallization rate of PLA. However, a persistent challenge remains in the form of phase separation or gradual migration of the blended soft polymer or plasticizers. To simultaneously enhance the miscibility of the blends and toughness of 3D-printed parts, a triblock copolymer PLA-PEG-PLA was synthesized and blended with PLA in varying proportions (5, 10, 15, and 20 wt %). Blending only 10-20 wt % low molecular weight PLA-PEG-PLA into PLA yielded a miscible blend that showed a 45-fold increase in elongation at break and a 23-fold enhancement in toughness over neat PLA. Scanning electron microscopy (SEM) images of fractured cross sections revealed a brittle to ductile transition in 3D-printed PLA/PLA-PEG-PLA samples. Isothermal crystallization studies and data analysis using the Avrami equation showed an enhancement in the crystal growth rate and overall rate of crystallization. The blends achieved half of their crystallinity in approximately 3 min, a significant improvement over the 9 min required by PLA alone. This underscores the efficiency of our approach. This was also evident in the spherulite growth of 3D-printed PLA and mPLA blends when examined using polarized optical microscopy (POM). To the best of our knowledge, this is the first report exploring the use of blends that include PLA and low molecular weight PLA-PEG-PLA triblock copolymers for 3D printing applications.
Keywords: Crystallization; FFF 3D printing; PLA-PEG-PLA triblock copolymer; poly(lacticacid); toughness

Extrusion 3D printing of intrinsically fluorescent thermoplastic polyimide: revealing an undisclosed potential - Kothavade, Premkumar; Kafi, Abdullah; Dekiwadia, Chaitali; Kumar, Viksit; Sukumaran, Santhosh Babu; Shanmuganathan, Kadhiravan; Bateman, Stuart (POLYMERS, 2024)
Keywords: Additive manufacturing; functional extrusion; high-performance polymers; thermoplastic polyimide

Enhancing asphalt pavement longevity through microcapsule-encapsulated rejuvenators: mechanical performance and self-healing evaluation - Gowda, Sachin; Behl, Ambika; Shanmuganathan, Kadhiravan; Gupta, Aakash (International Journal of Pavement Research and Technology, 2025)
Self-healing asphalt incorporating encapsulated rejuvenators presents a promising solution to extend pavement life by autonomously restoring binder functionality in aged or cracked regions. Calcium-alginate microcapsules encapsulating a commercially available bio-based rejuvenator available in the Indian market were synthesized (2–3 mm in diameter) and incorporated into Bituminous Concrete Grade-II asphalt mixtures at 0%, 0.5% and 1% (by aggregates weight). Capsules showed rupture strength > 18 N and thermal stability up to 200 °C. Microstructural (4D-XRM (X-ray Microscopy), Scanning Electron Microscopy (SEM), Brunauer-Emmett-Teller (BET)), chemical (Fourier Transform Infrared (FTIR), Energy-Dispersive X-ray Spectroscopy (EDAX), SARA) and mechanical (Indirect Tensile Strength (ITS), resilient modulus, dynamic creep, Semi-Circular Bending (SCB) healing) tests under unaged, short-term aged (STA) and long-term aged (LTA) conditions were performed. At 1% dosage, the Healing Index (HI) increased substantially (up to 58.03% for LTA), while volumetric, rutting and moisture resistance were not significantly affected. EDAX and SARA confirm targeted rejuvenator release under aging. These findings show that low dosages of Calcium alginate microcapsules can improve fracture recovery in aged asphalt mixtures without compromising initial performance, supporting their potential for self-healing pavements.